A criação e estabilização na paranoia e na esquizofrenia: aportes para a clínica psicanalítica. - Adeodato, Tereza Raquel Tomé (2016)
From the understanding of the formation of Freud’s theory about psychoses and theoretical and clinical advances proposed by Lacan in clinical psychoses, we intend to understand the differentiation of the creation process in two specific psychoses: paranoia and schizophrenia. The relationship between creation and stabilization will also give us the opportunity to understand possible consequences for the direction of their treatment of psychoses. In order to achieve this, we proposed at first to elucidate the establishment within the psychosis by taking into account two specific features: the relationship of creation with untriggered psychosis and its relationship with the stabilization in triggered psychosis. Then we deepen our study on the differential role of the creation in clinical cases in order to deepen and illustrate our study according to the psychoanalytic theory. Finally, we intended to weave the creative potential to conduct the treatment of both psychoses. Thus, understanding the role of creation in the treatment of psychosis and its relation to natural defense forms of each structure can potentially contribute to the conduct of the treatment, as well as to reflect on the position occupied by the analyst on the various cases of the psychotic structure.